Indonesian Interests in The Agricultural Negotiations Under The Doha Development Agenda: an Analysis of the "July 2004 Package" - Thom J. Achterbosch; Budiman Hutabarat; Nizwar Syafa’a; Frank W. van Tongeren (Jurnal Agro Ekonomi, 2004)
IndonesianSejak Agenda Pembangunan Doha WTO dirumuskan terjadi perkembangan arah liberalisasi pedagangan. Di negara-negara OECD, keinginan untuk mengurangi bantuan domestik tampaknya agak lamban dan sejumlah negara berkembang agak enggan membuka pasarnya. Pada “paket Juli 2004” sejumlah negara anggota menyetujui adanya pengecualian perubahan pada beberapa produk, produk khas (special product) bagi negara berkembang dan produk peka (sensitive product) pada negara maju. Dengan memilih ‘paket Juli 2004’ sebagai titik awal, makalah ini mencoba menganalisis kepentingan Indonesian dalam perundingan pertanian dalam Agenda Pembangunan Doha. Penelitian ini menggunakan model ekonomi perdagangan dan produksi (pangkalan data dan analisis GTAP) untuk mengidentifikasi kemungkinan dampak skenario liberalisasi global yang realistis dalam semangat ‘paket Juli 2004’ pada perekonomian Indonesia. Pada keadaan perdagangan yang sudah berlangsung agak liberal di Indonesia saat ini dampak menyeluruh yang diharapkan pada pendapatan nasional, perdagangan dan produksi bernilai positif, tetapi terbatas. Untuk Indonesian liberalisasi global pertanian menjanjikan prospek yang positif untuk minyak sayuran dan produk ternak. Diduga terjadi pengaruh negatif dalam upaya melindungi sektor beras dan gula, yang akan dapat dikelola dengan biaya lumayan dengan menentukan beras sebagai produk khas. Skema pelarangan impor atau kuota terbatas akan menimbulkan penurunan tingkat kesejahteraan secara nyata.EnglishEver since the WTO Doha Development Agenda was formulated, there has been mixed development in the direction of global trade liberalization. The ambitions on reforming domestic support in OECD countries seem to be moderate, at best, and a number of developing countries are less inclined to open their markets through improved access. Under ‘July 2004 package’ members now agree on far reaching exemptions from reforms in individual products (special products for developing countries and sensitive products for developed countries). Taking the ‘July 2004 package’ as a starting point, this paper tries to assess Indonesian interests in the agricultural negotiations under the WTO Doha Development Agenda. This study uses a large-scale economic model of trade and production (GTAP data base and analysis) to identify the possible impact of a realistic global liberalization scenario in the spirit of the ‘July 2004 package’ on the Indonesian economy. Given the prevailing quite liberal trade regime in Indonesia the expected overall impacts on national income, trade and production are positive, but rather limited. For Indonesian agriculture global liberalization offers positive prospects for vegetable oils and for animal products. There are small adverse effects on the protected rice and sugar sectors, which can be managed at modest costs by designating rice as special product (SP). An import ban or restrictive quota regime would entail significant welfare losses.